The Role of E-Wallet Use, Financial Literacy, Lifestyle, Self-Control, and Peer Conformity on Millennial Consumptive Behavior - Harahap, Khairunnisa; A.W., Jumiadi; Rizal, Muhammad; Thohiri, Roza (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study examines the role of e-wallet usage, financial literacy, lifestyle, self-control, and peer conformity in influencing consumptive behavior among millennials. Along with the growth of digital financial services, understanding the factors that drive consumptive behavior is becoming increasingly important. This study aims to analyze how these variables interact and influence millennials' spending habits, with a particular focus on e-wallet usage. The findings provide insights that can be used to develop strategies to promote responsible financial behavior in this demographic group.